Estradiol Increases Camp in the Oviductal Secretory Cells Through a Nongenomic Mechanism - Cardenas-Sankan, G; Orihuela-Diaz, P; Reuquen-Lopez, P; Diaz-Saldivar, P; Orostica, M (BioScientifica Ltd., 2014)
In the rat oviduct, estradiol (E2) accelerates egg transport by a nongenomic action that requires previous conversion of E2 to methoxyestrogens via catechol-O-methyltranferase (COMT) and activation of estrogen receptor (ER) with subsequent production of cAMP and inositol triphosphate (IP3). However, the role of the different oviductal cellular phenotypes on this E2 nongenomic pathway remains undetermined. The aim of this study was to investigate the effect of E2 on the levels of cAMP and IP3 in primary cultures of secretory and smooth muscle cells from rat oviducts and determine the mechanism by which E2 increases cAMP in the secretory cells. In the secretory cells, E2 increased cAMP but not IP3, while in the smooth muscle cells E2 decreased cAMP and increased IP3. Suppression of protein synthesis by actinomycin D did not prevent the E2-induced cAMP increase, but this was blocked by the ER antagonist ICI 182 780 and the inhibitors of COMT OR 486, G protein-? inhibitory (G?i) protein pertussis toxin and adenylyl cyclase (AC) SQ 22536. Expression of the mRNA for the enzymes that metabolizes estrogens, Comt, Cyp1a1, and Cyp1b1 was found in the secretory cells, but this was not affected by E2. Finally, confocal immunofluorescence analysis showed that E2 induced colocalization between ESR1 (ER?) and G?i in extranuclear regions of the secretory cells. We conclude that E2 differentially regulates cAMP and IP3 in the secretory and smooth muscle cells of the rat oviduct. In the secretory cells, E2 increases cAMP via a nongenomic action that requires activation of COMT and ER, coupling between ESR1 and G?i, and stimulation of AC. © 2014 Society for Reproduction and Fertility.